Strengthening Public Investment Management in the Eastern Caribbean Currency Union : Getting more bang for the dollar! - Mitchell, A. E. Wayne (IMF Working Papers; Working Paper, 2020)
The quality and stock of infrastructure vary widely across countries of the Eastern Carribbean Currency Union and are inadequate to achieve the desired higher growth and social development. Given relatively low investment rates in the region, one solution is to invest more. However this paper shows that governments can also narrow their infrastructure and service gaps significantly by improving expenditure efficiency and strengthening public investment management systems.